Use of medicinal plants by veterinary practitioners in Spain: A cross-sectional survey - Romero, Beatriz; Susperregui, Julen; Sahagún, Ana M.; Diez, M. José; Fernández, Nélida; García, Juan J.; López, Cristina; Sierra, Matilde; Díez, Raquel (Frontiers in Veterinary Science, 2022)
Medicinal plants have been used in veterinary medicine since ancient times, and they are gaining importance in Eastern Europe. The aim of this study was to conduct a survey on the use of medicinal plants in Spain. A cross-sectional study with an online questionnaire was carried out among Spanish small animal veterinarians, to evaluate the use patterns of medicinal plants and attitudes of professionals towards it. 313 veterinarians took part in the study. Most of them were female (80.2%) and age ranged 35-49 (49.5%). 80.3% of respondents use phytotherapy. Musculoskeletal and gastrointestinal disorders were those most frequently treated, with cannabis, aloe and thyme the most often medicinal plants used. The most common pattern of user was women working in clinics.